Kepemimpinan Kepala Madrasah dalam Peningkatan Mutu Guru di MAN 1 Mandailing Natal - Fadlilah Fadlilah; Summiyani Summiyani; Nur Anisyah (JMiE (Journal of Management in Education), 2024)
This study aims to describe the leadership of the school principal in improving the quality of teaching staff at MAN 1 Mandailing Natal. The research method used is qualitative, with data collected through observation, interviews, and documentation. The findings reveal that: (1) The principal enhances teacher quality by developing work programs, establishing organizational structures, and involving teachers and staff in decision-making through deliberation; (2) The challenges faced include limited opportunities for teachers to attend training programs, inadequate facilities and infrastructure, and some teachers’ difficulties in utilizing available resources effectively; (3) Efforts made by the principal include organizing teacher training, sending teachers to participate in professional development programs, forming Subject Teacher Forums (MGMP), motivating teachers through rewards, and conducting supervision of both teaching practices and administrative activities. This study emphasizes that participatory leadership and a focus on teacher competence development are crucial factors in improving the quality of education at MAN 1 Mandailing Natal.